In situ Preparation of Chitosan/ZIF-8 Composite Beads for Highly Efficient Removal of U(VI) - Liu, Lijuan; Yang, Weiting; Gu, Dongxu; Zhao, Xiaojun; Pan, Qinhe (Frontiers in Chemistry, 2019)
With the rapid growth of nuclear power generation and fuel processing, the treatment of nuclear industry wastewater has become a major problem, and if not handled properly, it will pose a potential threat to the ecological environment and human health. Herein, a chitosan (CS)/ZIF-8 composite monolithic beads with ZIF-8 loading up to 60 wt% for U(VI) removal was prepared, which can be easily removed after use. It possesses a very high adsorption capacity of 629 mg g-1 at pH = 3 for U(VI) and a well recyclability is demonstrated for at least four adsorption/desorption cycles. X-ray photoelectron spectroscopy (XPS) was carried out to study the adsorption mechanism between uranium and adsorbent, and the chelation of U(VI) ions with imidazole, hydroxyl and amino groups was revealed. This work shows that CS/ZIF-8 composite can be used as an effective adsorbent for uranium extraction from aqueous solution, and has a potential application value in wastewater.